Language, literacy, and culture as grade one teachers carry out national educational reform policies a Philippine ethnography - Adler, Martha A. (ProQuest Dissertations & Theses Global, 1997)
"This ethnographic study examines the instructional practices and social actions of six grade one teachers at one Philippine public central elementary school during the 1988-1989 school year. Specifically, the study examines language and literacy, culture shared across systems, and policy and practice within the framework of Philippine educational reform policies. There were three major findings of this study. First, language and literacy instruction in the English-Filipino bilingual classrooms observed was not of the nature that would help these Cebuano-speaking children develop abilities and/or meaningful competencies in reading, writing, and speaking English, Filipino, or Cebuano. The study documents a shared culture between teachers and children in and out of school. Yet, in school, salient aspects of the classroom instruction included participant structures that did not challenge children to produce language, but rather to reproduce it. Classroom discourse was restricted; reproductive performance was the measure of a successful lesson. Literacy instruction became confused with language instruction, and, was, ultimately, neglected. Second, events inside the classroom were affected by those outside as the school functioned as a cultural unit in which teachers and administrators carried out non-curricular social obligations on a regular basis. For example, hosting guests from the central office generally required time out for preparation of special meals and physical improvements in the classrooms. Time spent on these preparations resulted in instructional time lost for the children. Finally, this study documents how cultural understandings shared by members of the local school community were enacted so that educational reform goals were, paradoxically, both met and unmet. For example, the enrollment records of grade one children were manipulated so that they did not reveal the children who had failed or dropped out. This was succeeded by allowing "reserve" children to take the places of those who did not pass on to grade two. This study is significant because of the cultural implications for the ways in which teachers taught language and literacy. The study shows that the shared culture of the teachers, children, and administration actually impeded language and literacy instruction and learning."--Abstract